The Phenomenon of al Tasyabbuh: Birthday Celebration in the View of Students, Education and the Perspective of Ulama Based on Islamic Law - Dwi Fitria Al Husaeni; Mushfani Ainul Urwah; Seni Siti Inayah; Munawar Rahmat; Risris Hari Nugraha; Nurul Firdaus (Indonesian Journal of Multidiciplinary Research, 2022)
At this time among Indonesian Muslims, the phenomenon of tasyabbuh is often encountered, such as the celebration of Valentine's Day, the style of dress, birthday celebrations and many more. This study aims to analyze the opinion of Muslim students regarding birthday celebrations as an example of the tasyabbuh phenomenon in everyday life. This study analyzes the law of birthday celebrations in an Islamic perspective. The research method is a mixed method (quantitative and qualitative). The research was conducted in three stages, namely i) distributing questionnaires; ii) in-depth interviews with experts and iii) data analysis. Respondents consisted of 35 active university students in Indonesia and two religious’ teachers in the Padalarang and Cimahi areas, Indonesia. The results of this study indicate that there are two opinions about birthday celebrations. First, there are scholars who allow birthday celebrations as long as they do not violate Islamic law and second, there are scholars who argue that birthday celebrations are prohibited because they resemble Jews and Christians. Both opinions have a strong legal basis derived from the Qur'an and Hadith. By doing this research, it is hoped that every Muslim can be wise about the actions that will be taken by paying attention to the law in an Islamic perspective. Therefore, a Muslim does not just follow a culture without knowing the cause and effect of the act.